FASt single‐breathhold 2D multislice myocardial T1 mapping (FAST1) at 1.5T for full left ventricular coverage in three breathholds. Issue 2 (24th July 2019) - Huang, Li; Neji, Radhouene; Nazir, Muhummad Sohaib; Whitaker, John; Duong, Phuoc; Reid, Fiona; Bosio, Filippo; Chiribiri, Amedeo; Razavi, Reza; Roujol, Sébastien
Abstract : Background: Conventional myocardial T1 mapping techniques such as modified Look–Locker inversion recovery (MOLLI) generate one T1 map per breathhold. T1 mapping with full left ventricular coverage may be desirable when spatial T1 variations are expected. This would require multiple breathholds, increasing patient discomfort and prolonging scan time. Purpose: To develop and characterize a novel FASt single‐breathhold 2D multislice myocardial T1 mapping (FAST1) technique for full left ventricular coverage. Study Type: Prospective. Population/Phantom: Numerical simulation, agarose/NiCl2 phantom, 9 healthy volunteers, and 17 patients. Field Strength/Sequence: 1.5T/FAST1. Assessment: Two FAST1 approaches, FAST1‐BS and FAST1‐IR, were characterized and compared with standard 5‐(3)‐3 MOLLI in terms of accuracy, precision/spatial variability, and repeatability. Statistical Tests: Kruskal‐Wallis, Wilcoxon signed rank tests, intraclass correlation coefficient analysis, analysis of variance, Student's t ‐tests, Pearson correlation analysis, and Bland–Altman analysis. Results: In simulation/phantom, FAST1‐BS, FAST1‐IR, and MOLLI had an accuracy (expressed as T1 error) of 0.2%/4%, 6%/9%, and 4%/7%, respectively, while FAST1‐BS and FAST1‐IR had a precision penalty of 1.7/1.5 and 1.5/1.4 in comparison with MOLLI, respectively. In healthy volunteers, FAST1‐BS/FAST1‐IR/MOLLI led to different native myocardial T1 times (1016 ± 27 msec/952 ±22 msec/987 ± 23 msec, P  < 0.0001) and spatial variability (66 ± 10 msec/57 ± 8 msec/46 ± 7 msec, P  < 0.001). There were no statistically significant differences between all techniques for T1 repeatability ( P = 0.18). In vivo native and postcontrast myocardial T1 times in both healthy volunteers and patients using FAST1‐BS/FAST1‐IR were highly correlated with MOLLI (Pearson correlation coefficient ≥0.93). Data Conclusion: FAST1 enables myocardial T1 mapping with full left ventricular coverage in three separated breathholds. In comparison with MOLLI, FAST1 yield a 5‐fold increase of spatial coverage, limited penalty of T1 precision/spatial variability, no significant difference of T1 repeatability, and highly correlated T1 times. FAST1‐IR provides improved T1 precision/spatial variability but reduced accuracy when compared with FAST1‐BS. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2020;51:492–504.